Candida Spondylodiscitis: Diagnostic Dilemmas and Treatment Strategies - Kılınç, Tunahan; Yıldız Kaya, Sibel; Mete, Bilgül; Tabak, Fehmi (Cerrahpaşa Medical Journal, 2025)
Spondylodiscitis is a serious and potentially life-threatening infection that affects the vertebrae and intervertebral discs. Candida spp. is a fungus that normally exists as a commensal organism in the human body but can become an opportunistic pathogen in individuals with weakened immune systems. Risk factors such as immunodeficiency, prolonged antibiotic use, intravenous drug use, diabetes, and alcohol dependency can contribute to the development of fungal spondylodiscitis. Fungal spondylodiscitis has a more insidious onset and presents with more ambiguous symptoms compared to bacterial cases, which can lead to delays in diagnosis and treatment. Patients typically present to the clinic with non-specific symptoms such as back pain, limited mobility, and sometimes fever. Because laboratory findings are generally non-specific, magnetic resonance imaging is considered an effective method for diagnosis. Definitive diagnosis typically relies on biopsy and culture results; however, cultures may be negative, and situations where biopsy is not always feasible make diagnosis more challenging. Conservative treatment is the gold standard; however, surgery can be performed when necessary. A multidisciplinary approach and individualized treatment plans are critically important in enhancing the effectiveness of therapy. In conclusion, Candida spondylodiscitis is a rare but severe infection. Mortality and morbidity rates can be reduced with early diagnosis and appropriate treatment strategies. In clinical practice, the possibility of fungal infection should not be overlooked, especially in patients with risk factors and should be actively investigated during the diagnostic process. This article aims to contribute to a better understanding of spondylodiscitis caused by Candida spp. Cite this article as: Kılınç T, Yıldız Kaya S, Mete B, Tabak F. Candida spondylodiscitis: diagnostic dilemmas and treatment strategies. Cerrahpaşa Med J 2025; 49, 0071, doi: 10.5152/cjm.2025.24071.